Ultrasound in trauma resuscitation and critical care with hemodynamic transesophageal echocardiography guidance. Issue 1 (July 2019) - Nowack, Timothy; Christie, D. Benjamin
Abstract : BACKGROUND: Volume replacement strategies and resuscitation endpoints of therapy in the critical ill or injured patient continues to be a heavily debated topic despite decades of research and the ever evolving technologies that provide for alternate methods of monitoring. Hemodynamic transesophageal echocardiography (hTEE), refined for the use in the intensive care unit (ICU), allows for direct visualization of cardiac filling and function, enabling real-time guidance in the resuscitation of critically ill patients. The disposable, 17F hTEE probe can remain indwelling for up to 72 hours, providing continuous, unobstructed assessments of cardiac activity via the transgastric short axis, midesophageal four chamber, and superior vena cava views. With such, preload and contractility, ventricular size and function, and volume responsiveness can be accurately evaluated and trended for change over time. Hemodynamic transesophageal echocardiography as a monitoring modality is becoming more pervasive in ICUs on a worldwide scale, allowing for real-time visualization of resuscitation and its therapeutic effects, a better understanding of resuscitation effects on individual patients, a more rapid conclusion to patient's resuscitation needs and provides the physician more confidence and patience in guiding complex volume resuscitations. RESULTS: This presentation will focus on discussing practical applications of the hTEE system and its benefits in critical care management. We will review four patients at our facility admitted to the ICU due to hemodynamic instability of varying etiologies that required volume resuscitation. With the videos, we will demonstrate how hTEE can guide patient therapy, often counter-intuitively, in the critically ill using the three basic cardiac views. Specific scenarios and hTEE videos include: (1) volume resuscitation in Acute Respiratory Distress Syndrome (ARDS), (2) volume resuscitation guided by hTEE, (3) underresuscitation in a "routine" trauma case, and (4) deescalation of therapy by weaning of high-dose vasopressors using hTEE monitoring. CONCLUSION: Hemodynamic transesophageal echocardiography is an excellent hemodynamic monitoring modality for the intensivist and has many practical applications in the management of the critical ill or injured patients. Hemodynamic transesophageal echocardiography has demonstrated that patient's resuscitation needs are often underestimated and that a more tailored approach to volume delivery is achievable, a particular benefit in the older and more comorbid patient. Future applications of hTEE include CRRT volume management, organ donor hemodynamic optimization, and postresuscitation monitoring in trauma patient requiring massive transfusion protocol. These videos demonstrate examples of the benefits of real-time cardiac monitoring, which allowed for guided resuscitation and improved patient outcomes. LEVEL OF EVIDENCE: Procedures and techniques, level IV. Abstract : Supplemental digital content is available in the text.